Association of the nematophagous fungi Arthrobotrys musiformis and Monacrosporium sinense in vitro and in vivo for biological control of equine cyathostomins - Dalcin Júnior, Atílio; Ferreira, Vinicius Monteiro; de Carvalho, Lorendane Millena; Álvares, Felipe Boniedj Ventura; Vilela, Vinicius Longo Ribeiro; Ferraz, Carolina Magri; Veloso, Francielle Bosi Rodrigues; Lima, Thalita Fonseca; Braga, Fabio Ribeiro; de Araújo, Jackson Victor (Brazilian Journal of Veterinary Medicine, 2021)
The fungi Arthrobotrys musiformis (A144 isolate) and Monacrosporium sinense (SF53 isolate) were evaluated for controlling L3 of cyathostomins. In vitro, Petri dishes containing 2% water-agar were divided into groups: 1 (A144 + SF53); 2 (SF53); 3 (A144); 4 (control group). In vivo, 24 animals received pellets containing fungal mycelium. The animals were divided into four groups: 1 (100 g of pellets containing A144 + SF53 isolates); 2 (100 g of pellets containing A144 isolate); 3 (100 g of pellets containing SF53 isolate); 4 (Pellets without fungi). Feces were collected at 12, 24, 36, 48, 60 and 72 hours after pellet administration. The association of isolates, in vitro, was able to reduce L3 by 69.7%, compared with the control group; A144 isolate reduced L3 by 77.3%; and SF53 isolate reduced L3 by 84.3%. In vivo, the association of fungi A. musiformis and M. sinense showed predatory activity against L3 of cyathostomins with efficacy ranged from 63.2% to 83%. The association of the fungi A. musiformis and M. sinense both in vitro and in vivo proved to be efficient for controlling L3 of cyathostomins.